Theoretical Aspects of Soil Layer Turnover Within the Boundaries of Its Own Furrow - Ya. P. Lobachevsky; V. V. Sharov; N. V. Aldoshin; Yu. S. Tsench; A. S. Zolotarev (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that soil layer turnover remains the most widely used method of primary tillage. Among the existing techniques, smooth plowing without producing back ridges or furrows, which is achieved using reversible plows, best meets the high standards of modern agricultural practices. (Research purpose) The study aims to substantiate the kinematics of soil layer turnover within the boundaries of its own furrow without lateral displacement. (Materials and methods) In analyzing the kinematics, the soil layer is assumed to behave as a cohesive elastic substance undergoing deformation during turnover within its own furrow, without disintegration. This assumption is quite reasonable, as it is well-established that a sodded and moist layer can be extracted as a continuous, intact strip that retains its geometric dimensions when turned 180°. The trajectory of the layer is derived using classical methods of theoretical mechanics. (Results and discussions) The equations governing the motion of the soil layer points during turnover within its own furrow are analyzed. During this process, all points in the cross-section of the layer undergo spatial displacement. Changes in displacement, velocity, and acceleration of the i-th point of the hypothetical layer exhibit smooth dependencies described by trigonometric functions. However, at a rotation angle of ωt = π/2, an abrupt change occurs in the trajectories of displacement, velocity and acceleration graphs, indicating sharply variable loads acting on the soil layer at this point. The abrupt change is attributed to a shift in the support rib which serves as the axis for the rotation of the soil layer's crosssection. The center of gravity of the cross-section moves with variable velocity and acceleration, which indicates the presence of inertial forces. Overcoming these forces requires a certain amount of energy. (Conclusions) The energy required largely depends on the geometric parameters of the layer a, b and its rotation modes (ω). When the layer cross-section rotates by an angle When the layer cross-section rotates by an angle ωt = π/2 – γ, the vertical acceleration of the central point (О) reaches its maximum value. Under certain conditions, the soil layer may detach from the furrow bottom in this position. The kinematics analysis of a soil layer turnover within the boundaries of its own furrow reveals new phenomena occurring during its motion to identifies the patterns of influence that the soil layer's geometric parameters exert on its dynamic characteristics.